move the -5 over by adding 5 to both sides
3x^2+4x+5=0
must use quadratic formula
for an equation in the form
ax^2+bx+c=0
x=[tex] \frac{-b+/- \sqrt{b^2-4ac} }{2a} [/tex]
a=3
b=4
c=5
x=[tex] \frac{-4+/- \sqrt{4^2-4(3)(5)} }{2(3)} [/tex]
x=[tex] \frac{-4+/- \sqrt{16-60} }{6} [/tex]
x=[tex] \frac{-4+/- \sqrt{-44} }{6} [/tex]
x=[tex] \frac{-4+/- 2\sqrt{-11} }{6} [/tex]
remember that√-1=i
x=[tex] \frac{-4+/- 2i\sqrt{-11} }{6} [/tex]
x=[tex] \frac{-2+/- i\sqrt{-11} }{3} [/tex]
x=[tex] \frac{-2+ i\sqrt{-11} }{3} [/tex] or x=[tex] \frac{-2- i\sqrt{-11} }{3} [/tex]